THE SOCIAL SUPPORT AND PREVALENCE EMESIS GRAVIDARIUM ON PREGNANT MOTHER IN TRIMESTER I AT PUSKESMAS KEMBARAN I BANYUMAS REGENCY - Devita Elsanti; Siti Nurjanah; Happy Dwi Aprilina (UNEJ e-Proceeding)
Maternal Mortality Rate (MMR) served asa basis or benchmark for the country's welfare.Based on estimation made from the Demographicand Health Survey Indonesia (IDHS) 1990 to 2007,it showed that the maternal mortality ratio (MMR)in Indonesia in 2015 reached 161 / 100,000 livebirths, while the MDG targets Indonesia is 102 /100,000 live births (Health Dept, 2013). The datafrom WHO Maternal Mortality Rate (MMR) inIndonesia in 2013 shows that as many as 8,800 bythe Maternal Mortality Ratio (MMR) of 190 (120-300) per 100,000 live births (WHO, 2013). Thematernal mortality rate in Central Java Province in2012 based on reports from regency / city was116.34 / 100,000 live births, an increase comparedwith MMR in 2011 was 116.01 / 100,000 livebirths. Most maternal deaths are in Brebes with 51deaths. Salatiga is the Regency with the leastnumber of maternal deaths with only 2 cases.According to the Central Java Provincial HealthOffice, there were 32 maternal deaths (CentralJava Health Office, 2012). Additionally, it wasnoted that there were maternal mortality by 711cases and in 2015 there were 115 cases in 2014(Nurdin, 2015).The reason of the high death toll inIndonesia is due to the low quality of life, theaverage low education, health status and poornutrition, anemia, iron deficiency, and theincidence of chronic malnutrition (Amaludin,2015). Pregnant women are in need of adequatenutrition even doubled because nutrition is neededby pregnant women to meet the needs not only forthe fetus but also the mother. However,sometimes pregnant women experience nauseaand excessive vomiting so that nutrition cannot befulfilled. Rose & Neil (2006) states that emesisgravidarium in pregnant women can cause avariety of negative effects, one of which is adecrease in appetite that result in changes in theelectrolyte balance of potassium, calcium, andsodium, causing changes in the body's metabolism.It affects the fetus, it will be lack of nutrients andfluids needed by the body, the baby will be bornwill be in low birth weight and impaired growthprocess. Excessive nausea and vomiting can alsoreduce body fluid, so that the blood becomes thick(hemoconcentration) and blood circulation totissues is late. If that happens, then theconsumption of oxygen and nourishment to thetissues also reduced (Anggarani and Subekti, 2013,Jeffrey et al, 2003). Lack of oxygen and food to thenetwork will cause tissue damage that couldreduce maternal health and fetal development inthe womb. In such cases, it needs serioustreatment (Hidayati, 2009).The purposes of this research are:1. To find out the characteristics of pregnantwomen consisting of age, education level andoccupation.2. To find out the status of social support forpregnant women in the first trimester inPuskesmas Kembaran I Banyumas.3. To find out the incidence of emesis gravidariumin the first trimester pregnant women inPuskesmas Kembaran I Banyumas.4. To find out the correlation between socialsupport and emesis gravidarium in the firsttrimester of pregnant women in PuskesmasKembaran I Banyumas.